Summative Assessment of Islamic Education Subject in Merdeka Curriculum - Fitria, Nabila Nayyirotul; Mufidah, Luk Luk Nur; Setiawati, Puput (Journal of Educational Research and Practice, 2024)
The objective of this research is to examine the implementation of summative assessment within the “Merdeka” Curriculum, specifically in Islamic Religious Education courses. The adoption of this curriculum is still relatively new in the education process, and many teachers have not yet achieved optimal success in applying it. Although this assessment closely resembles that of the previous curriculum, it requires alignment with learning indicators and individual student characteristics to accurately reflect learning objectives. This study employs a qualitative descriptive methodology, gathering data from library research. The primary reference for this research is the “Merdeka Belajar” curriculum strategy from the Ministry of Education and Culture of the Republic of Indonesia. Summative assessment refers to evaluations conducted at the end of an academic year or semester. For the successful implementation of summative assessment in Islamic Religious Education within the Merdeka Curriculum, this research identifies nine essential phases: (1) defining competencies; (2) selecting an assessment structure; (3) providing necessary assessment tools; (4) establishing an assessment scale; (5) scheduling assessments; (6) completing summative assessments on time; (7) processing assessment results; (8) providing feedback and reports; and (9) conducting an evaluation.